Clinical and Histopathological Findings in Patients Who Underwent Splenectomy: A Ten-Year Study in Iran - Arash Dehghan; Nika Eskandari; Nakisa Niknejad (Acta Medica Iranica, 2020)
Objective: The description of histopathological features of spleen specimens in those undergoing splenectomy is necessary and even vital for selecting the best patient's diagnostic and therapeutic management. However, in some cases, the histological findings of those with dramatic clinical presentation may be imperceptible and vice versa.